Exon Nomenclature And Classification of Transcripts (ENACT) provides a systematic framework to annotate exon attributes - Verma, Paras; Thakur, Deeksha; Awasthi, Deepanshi; Pandit, Shashi Bhushan (Genome Research, 2025)
Isoform diversity is known to enhance a gene's functional repertoire by producing protein variants with distinct functional implications. Despite numerous studies on transcriptome diversifying processes (alternative splicing/transcription), understanding their extent and correlated impact on proteome diversity remains limited owing to dearth of subsequent proteogenomic consequences. To coalesce the genomic information embedded in exons with isoform sequences, we present an innovative framework, “Exon Nomenclature And Classification of Transcripts” (ENACT). This centralizes exonic loci such that protein sequence information is integrated (onto the available/annotated or new transcripts) while enabling tracking and assessing splice-site variability through unique yielded descriptors. The resulting annotation from the ENACT framework enables exon features to be tractable, facilitating a systematic analysis of isoform diversity. Our findings and case studies unveil systemic exon inclusion roles in regulating diversity in coding region. Correspondingly, annotation of protein-coding genes and associated transcripts from C. elegans, D. melanogaster, D. rerio, M. musculus, and H. sapiens are publicly accessible in a dedicated resource.
10.1101/gr.279878.124